UNDERSTANDING THE LONG-TERM DYNAMICS AND DYNAMIC RESPONSES IN COMMERCIAL BANK CREDIT: A COMPREHENSIVE ECONOMIC ANALYSIS - Mubarok, Faizul; Febrina, Anisha; Astuti, Desy Widhi; Ferliana, Vira (Universitas Muria Kudus, 2025)
This paper investigates the long-term equilibrium relationship and dynamic responses of economic variables to changes in commercial bank credit, emphasizing foreign direct investment (FDI) and non-performing loans (NPL). The study also examines how bank credit dynamics respond to shocks from other economic variables, such as interest rates and inflation. Using a vector error correction model (VECM) to analyze time series data, the findings reveal a significant long-term equilibrium among FDI, NPL, and commercial bank credit, offering insights into their interrelationships. The results highlight the importance of understanding these dynamics for stakeholders as they illuminate the variability of commercial bank credit. Furthermore, the research underscores the need for banks to consider the impacts of interest rate fluctuations and inflation on credit dynamics, equipping stakeholders with tools to identify risk-oriented features in a dynamic economic environment. However, the study is limited by its focus on a specific period and geographic region, which may affect the generalizability of the findings. Future research should consider incorporating more diverse datasets and exploring additional factors influencing bank credit dynamics. Overall, this study enhances the understanding of long-term interconnections among these economic variables, providing valuable insights for developing effective economic policies.